Squamous cell carcinoma on an arteriovenous fistula scar: case report - da Silva Grillo, Vinicius Tadeu Ramos [UNESP]; Mellucci Filho, Pedro Luciano [UNESP]; Lopes Soares, Marina Moraes [UNESP]; Sertorio, Nathalia Dias [UNESP]; Jaldin, Rodrigo Gibin [UNESP]; Sobreira, Marcone Lima [UNESP]; de Campos, Eloisa Bueno Pires [UNESP]; Bertanha, Matheus [UNESP] (FapUNIFESP (SciELO), 2023)
The main type of access used for hemodialysis is the arteriovenous fistula (AVF) because it offers superior patency and lower complication rates when compared to other hemodialysis accesses. We report the case of a 69-year-old female patient with chronic kidney disease on dialysis secondary to hypertensive nephrosclerosis with a radiocephalic AVF in the left upper limb created 9 years previously. Two years previously, she had undergone a kidney transplant and was taking immunosuppressants. A crusted lesion developed on her left forearm with onset 3 months before presentation and she underwent an excisional biopsy that revealed a well-differentiated and superficially invasive squamous cell carcinoma, with lateral and deep surgical margins free from neoplasia. At 1-year follow-up, the patient showed no signs of neoplastic recurrence.
Carcinoma espinocelular sobre cicatriz de fístula arteriovenosa: relato de caso
Keywords: arteriovenous fistula; skin neoplasms; squamous cell carcinoma